Low-Code and the Democratization of Programming - Team, O'Reilly (O'Reilly Media, Inc., 2021)
Low-code is one of the fastest growing areas of software development today. An increasing number of PaaS companies now offer low-code solutions for data manipulation, integration, and transformation; and the shift toward low-code solutions is poised to unleash a new democratization of programming. What's happening to make computing power more widely accessible? Will this new low-code level of abstraction allow programmers to be more creative? This report examines how the low-code model is democratizing programming, changing everyday programmer roles, liberating teams, and introducing new dimensions of creativity--and challenges--in software development. As more people learn how to be creative with low-code, what new kinds of programming--and programmers--will emerge as a result? This report covers: What low-code and no-code platforms are--and how they'll democratize programming and transform programmer roles The potential challenges low-code solutions may introduce to software development What new kinds of approaches to programming will emerge as low-code use grows How low-code solutions may allow programmers to think more creatively about programming and software development.